Amines: possible causative agents in the development of bronchial hyperreactivity in workers manufacturing polyurethanes from isocyanates. Issue 3 (August 1983) - Belin, L; Wass, U; Audunsson, G; Mathiasson, L
Abstract : Investigations of respiratory symptoms among workers in a factory producing polyurethane foam included measurement of air pollution with amines and isocyanates and a simultaneous health investigation of the exposed workers. An increased bronchial reactivity to inhaled methacholine was found in the study group compared with two unexposed control groups. This finding, together with visual disturbances in the exposed group, were assumed to be caused mainly by the volatile amines. The concentrations of isocyanates in air were well below 0.005 ppm. The amine concentration was 1000 to 10 000 times higher than the isocyanate concentration. The most volatile amine, N-methylmorpholine, occurred in the air in concentrations higher than 10 ppm. The results indicate that not only the isocyanates but also the amines might well be responsible for respiratory symptoms among exposed workers in polyurethane foam production.